Studies in Health technology and Informatics Volume 29 - Medicine Meets Virtual Reality Health Care in the Information Age - Weghorst, Suzanne J. (IOS Press, 2014)
Plowing through this year's MMVR contributions I am struck by the following: • the depth of their creativity and willingness to explore uncharted waters • the breadth of our diversity, both geopolitically and conceptually • the extend to which we are both producers and consumers of these innovations Each year we leapfrog ourselves toward the horizon. In four years our review process has moved from titles to abstracts to printed manuscripts to HTML documents. Our presentations, posters, and exhibits have increased in both quantity and quality. And with each year our visions have moved closer to everyday practice.